PENINGKATAN MOTIVASI BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL INTERAKSI SOSIAL DI KELAS 4 MIS TERPADU ALHIJRAH BINTUJU - Laswardi Laswardi; Sri Handayani Hasibuan; Asfiati Asfiati (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This study aims to find out the overview of the use of social interaction models in increasing student learning motivation in science and science subjects. Based on the results of data analysis, it was found: 1) The results of the study that have been explained that the learning process of IPAS before the social interaction model was applied had a low percentage level. The score obtained was only 18.18% who got a complete score with the number of students 4 students out of 22 students. 2) The results of the next research, the learning process of IPAS during the application of the social interaction model on the energy materials around us has experienced a significant improvement. In the first cycle, learning outcomes increased with a percentage of 31.82% with the number of students who completed 7 students. Meanwhile, in the second cycle, the learning outcome was 77.27% with the number of students who completed as many as 17 students out of 22 students in class 4MIS Integrated Alhijrah Bintuju. From this data, the results obtained were that the research conducted using the social interaction learning model was successfully carried out with a satisfactory score and passed the KKM score of 75. 3) The completeness of students before treatment reached (18.18%), while in cycle 1 after the treatment of completeness of students reached (31.82%), and in cycle II the completeness of students increased to reach (77.27%).